2015
DOI: 10.1002/14651858.cd010037.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation for prevention of primary hypertension

Abstract: Calcium supplementation for prevention of primary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 64 publications
2
76
1
4
Order By: Relevance
“…Higher levels of parathyroid hormone and DHVD stimulate calcium influx into different cell types and increase intracellular calcium into the vascular smooth muscle cell, and consequently increased muscle reactivity, peripheral vascular resistance, and thus higher blood pressure. 18,19 In order to effectively implement the WHO recommendations and reduce the risk of hypertensive disorders of pregnancy in the most vulnerable women, it is essential to identify the specific populations or subpopulations at higher risk. This would allow the evidence-based priorisation of calcium supplementation, and would inform the development of policies, strategies, and actions, including a population-specific quantity assessment of the additional calcium intake required.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of parathyroid hormone and DHVD stimulate calcium influx into different cell types and increase intracellular calcium into the vascular smooth muscle cell, and consequently increased muscle reactivity, peripheral vascular resistance, and thus higher blood pressure. 18,19 In order to effectively implement the WHO recommendations and reduce the risk of hypertensive disorders of pregnancy in the most vulnerable women, it is essential to identify the specific populations or subpopulations at higher risk. This would allow the evidence-based priorisation of calcium supplementation, and would inform the development of policies, strategies, and actions, including a population-specific quantity assessment of the additional calcium intake required.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, according to Bucher et al [37], a high intake of calcium in subjects with high adherence to the DASH diet may act as a modulating factor of BP levels, specifically decreasing systolic BP, although this speculation remains controversial. In their review of randomized clinical trials, Cormick et al [38] indicated that abundant calcium intake slightly reduced systolic BP and diastolic BP, especially in normotensive young adults. On the other hand, a higher intake of fruits, vegetables, and legumes, together with less SFA and more monounsaturated fatty acid consumption, may explain the beneficial effects of the DASH diet on the parameters of abdominal fat and visceral fat accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…38 The authors of the most recent meta-analysis, published in 2015, analyzed the results of 16 clinical trials (n=3048) with exclusively normotensive subjects. 39 Once again, a modest yet significant effect was found (SBP mean difference [MD] −1.43 mmHg, 95% CI −2.15 to −0.72; DBP MD −0.98 mmHg, 95% CI −1.46 to −0.50). The mechanism by which calcium may reduce BP has not been confirmed; however, it has been suggested that when adequate amounts of calcium are consumed, the entry of calcium into cells is inhibited and as a consequence vasoconstriction is attenuated.…”
Section: Black Cumin Seeds (Nigella Sativa)mentioning
confidence: 95%